1996
DOI: 10.1021/jo951025x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Reaction of Oxaphosphetanes Derived from Benzaldehyde and 1-Adamantylmethylidene Ylide

Abstract: The Wittig reaction of (1-adamantylmethylidene)triphenylphosphorane (Ph(3)P=CH(1-Ad)) with benzaldehyde was investigated, and the results were compared with those of other ylides. The substituent effect in the reaction of the ylide with benzaldehydes was determined by competition experiments, which gave a Hammett rho value of 3.2. The rho value is much larger than those reported for analogous reactions of Ph(3)P=CH(CH(2))(2)CH(3) (rho = 0.20) and Ph(3)P=CH(CH(3))(2) (rho = 0.59), indicating that the reaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As expected, when 1b (1 equiv) reacted with 11 (6 equiv) and 2 (3 equiv) in the presence of the oxygen within 5−10 min, the only product is ( E )-1-adamantyl-2-(4-methoxyphenyl)ethene 12 and the yield is 100% when the crude mixture was analyzed by the proton NMR (eq 4). This result indicates that the same adamantyl radical actually could be generated by using 11 , 2 , and air at room temperature. ,
…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…As expected, when 1b (1 equiv) reacted with 11 (6 equiv) and 2 (3 equiv) in the presence of the oxygen within 5−10 min, the only product is ( E )-1-adamantyl-2-(4-methoxyphenyl)ethene 12 and the yield is 100% when the crude mixture was analyzed by the proton NMR (eq 4). This result indicates that the same adamantyl radical actually could be generated by using 11 , 2 , and air at room temperature. ,
…”
Section: Resultsmentioning
confidence: 62%
“…It has been reported that different alkyl radicals including 1-adamantyl radical and aryl radical can be generated by the reduction of alkyl or aryl halides with (ethylenediamine)chromium(II) complexes in dry dimethylformamide . The palladium-catalyzed reaction of 1-bromoadamantane with styrene and donor-substituted styrenes give the corresponding Heck-type coupling product ( E )-1-adamantyl-2-arylethene in 15−41% also has been reported by Bräse et al Similarly, Yamataka and co-workers also have reported that both ( Z ) - and ( E )-1-adamantyl-2-arylethene mixture had been prepared from the Wittig reaction of substituted benzaldehydes with (1-adamantylmethylidene)triphenylphosphorane …”
Section: Resultsmentioning
confidence: 67%
“…Relative overall reaction rates for the examined reaction were determined by experiments using competition Hammett methodology . The ratios of particular vinylphosphonium salts 10 were determined from their yields when α‐tributyl‐ [(trimethylsilyl)‐methylene]phosphorane 8 were allowed to compete with benzaldehyde 9a and with one or two selected p ‐substituted derivatives 9b–j in the same reaction mixture.…”
Section: Resultsmentioning
confidence: 99%